REVISITING HYALURONIC ACID THERAPY IN ORTHOPEDICS: BETWEEN SCIENCE AND SKEPTICISM - Piotr Armański; Katarzyna Herjan; Gabriela Łocik; Marta Bonarska; Joanna Wróbel; Katarzyna Kozon; Klaudia Jedlina (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Hyaluronic acid (HA) is a long, unbranched polysaccharide classified as a glycosaminoglycan. Since its isolation from the vitreous body of an ox in 1934 by Karl Meyer and John Palmer, HA has attracted considerable interest across medical disciplines. Naturally occurring HA possesses several favorable properties, including high water-binding capacity, biocompatibility, viscoelasticity, free radical scavenging, and unique rheological characteristics. It also exhibits anti-inflammatory, antiangiogenic, and immunosuppressive effects, contributing to its increasing popularity—especially in orthopedics. HA is present in high concentrations within synovial fluid, joint capsules, and cartilage, making it highly relevant in conditions involving joint degeneration or injury. Accordingly, HA-based therapies have found widespread application in treating osteoarthritis, rheumatoid arthritis, tendinopathies, and other soft tissue disorders. Aim: The aim of this work is to evaluate the clinical relevance, efficacy, and safety of hyaluronic acid (HA) in the treatment of orthopedic conditions, particularly osteoarthritis, tendinopathies, and other soft tissue injuries. The objective is to clarify HA’s therapeutic value, especially via intra-articular injection, amid ongoing debate regarding its clinical effectiveness compared to placebo and standard non-surgical treatments. Materials and Methods: This review is based on an analysis of numerous studies, particularly randomized controlled trials (RCTs), that assessed the efficacy of HA in orthopedic applications. Emphasis was placed on comparing HA treatment outcomes—most notably intra-articular injections—with those of placebo and conventional non-operative therapies. Literature was reviewed from relevant medical databases and peer-reviewed sources. Results: Evidence from multiple studies suggests that intra-articular HA injections can lead to improvements in pain and joint function compared to baseline or non-surgical treatments. However, many randomized controlled trials have shown no statistically significant advantage of HA over placebo. Despite this, patient-reported outcomes often indicate symptom relief and improved function following HA administration. Conclusion: Due to conflicting data regarding its clinical utility, the use of HA in orthopedics remains a topic of ongoing debate. Nonetheless, HA’s favorable safety profile and biological properties support its consideration in selected orthopedic cases. When used appropriately, HA injections may offer a viable non-surgical option for managing joint and soft tissue disorders.